(untitled) (Edad Media. Revista de Historia, 2017)
In the late fifteenth century, the Catholic Monarchs decided to encabezar the almojarifazgo of Cordoba, that is, to burden, among other things, foreign trade within the fiscal jurisdiction of the Kingdom and Bishopric of Cordoba. With the aid of the relevant documents, we can analyze certain aspects of the city’s commercial activity that have hitherto been neglected given the scarcity of sources. This paper will, therefore, study the customs duties themselves and their collection, as well as the traders, their personal and professional relationships, and the goods treated.